Pembuatan Sabit Panjang 300 mm, Lebar 50 mm, Tebal 5 mm Kapasitas 0,5 Unit/Jam - Ahmad Alvino Satria Gama Ramadhani; Syamsul Hadi; Muhammad Firman Agustianto; Kafii Widhyadhana; Nayyaka Kalingga Putra (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Broken, bent, and fast wear of farmer's sickle as a problem in its use. The purpose of making is to get a sickle that is not easily broken, not easily bent, and relatively wear resistant. The manufacturing method is through: sickle design measuring 300x250 mm with a sickle width of 50 mm, and a thickness of 5 mm thinning towards the sharp side of the sickle, turning the teak wood handle, trial cutting of medium carbon steel material, AISI 1045 size 20 x 25 x 6 mm or equivalent to 3000 mm3, forging at a temperature of 800-1000 ° C, hardening into a water cooling medium, making a locking ring with copper welding, turning the wooden handle, installing a steel locking ring between the sickle root and the wooden handle, finishing with painting the handle according to the order, and checking the quality and dimensions. The result of the production is a sickle with dimensions of 300x250 mm with a width of 50 mm, and a thickness of 5 mm with a wooden handle, the manufacturing cost is IDR 84,000/unit which requires a production time of 120 minutes/unit which has an impact on the use of the sickle for cutting grass and the like, it can be used for up to around 4 years.